Commensal Rodent Habitat Expansion Enhances Arthropod Disease Vectors on a Tropical Volcanic Island - Wu, De-Lun; Shih, Han-Chun; Wang, Jen-Kai; Teng, Hwa-Jen; Kuo, Chi-Chien (Frontiers in Veterinary Science, 2021)
On volcanic islands, the release of animals from predators and competitors can lead to increased body size and population density as well as the expanded habitat use of introduced animals relative to their mainland counterparts. Such alterations might facilitate the spread of diseases on islands when these exotic animals also carry pathogenic agents; however, this has rarely been investigated. The commensal Asian house rat (Rattus tanezumi) is confined to human residential surroundings in mainland Taiwan but can be observed in the forests of nearby Orchid Island, which is a tropical volcanic island. Orchid Island is also a hotspot for scrub typhus, a lethal febrile disease transmitted by larval trombiculid mites (chiggers) that are infective primarily with the rickettsia Orientia tsutsugamushi (OT). We predicted an increase in chigger abundance when rodents (the primary host of chiggers) invade forests from human settlements since soils are largely absent in the latter habitat but necessary for the survival of nymphal and adult mites. A trimonthly rodent survey at 10 sites in three habitats (human residential, grassland, and forest) found only R. tanezumi and showed more R. tanezumi and chiggers in forests than in human residential sites. There was a positive association between rodent and chigger abundance, as well as between rodent body weight and chigger load. Lastly, >95% of chiggers were Leptotrombidium deliense and their OT infection rates were similar among all habitats. Our study demonstrated potentially elevated risks of scrub typhus when this commensal rat species is allowed to invade natural habitats on islands. Additionally, while the success of invasive species can be ascribed to their parasites being left behind, island invaders might instead obtain more parasites if the parasite requires only a single host (e.g., trombiculid mite), is a host generalist (e.g., L. deliense), and is transferred from unsuitable to suitable habitats (i.e. human settlements on the mainland to forests on an island).